Teaching Computational Physics in Undergraduate Physics Education: A Narrative Review and Implications for Pre-Service Teachers - Muhammad Taufik; Hikmawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
Computational methodologies are now a fundamental part of applied science and are considered part of the teaching of the discipline of science. Because computation adds another level of engagement to the theoretical and experimental approaches of a discipline, teaching education programs in the science disciplines, particularly pre-service physics teachers, are required to use computational techniques and engage in modeling practices. Yet, the teaching practices and pedagogical techniques that are being employed for the teaching of computational physics in teacher education are \not consistent or widely utilized. This study uses narrative literature review techniques to study the teaching of computational physics in undergraduate physics education programs, especially regarding pre-service physics teachers. The literature under examination in this review comes from international peer-reviewed journals in the education fields of physics and science published within the years of 2020 to 2025. The review uses thematic analysis to show that there are three most common teaching models in use, those being: 1. teaching computational physics as a separate discipline, 2. the teaching of partial computational practices within standard physics courses, and 3. the teaching of computational practices in all courses of the undergraduate curriculum. The results of this review show that even the teaching of computational physics most likely uses pedagogical techniques that focus on project based learning, modeling, and the use of software such as Python and interactive simulations for learning. Such techniques likely enhance the understanding of the pre-service teachers’ pedagogical content knowledge as they learn computational thinking. They recommend that teacher education programs integrate computational physics in a systematic and manageable way to promote digitally enhanced learning environments for future physics teachers.